Pengaruh Rasio Profitabilitas dan Firm Size Terhadap Nilai Perusahaan Pada Perusahaan Manufaktur Sub Sektor Otomotif dan Komponen Yang Terdaftar Di Bursa Efek Indonesia Periode Tahun 2016-2020 - Amalia, Restu (Pascasarjana Universitas Primagraha, 2023)
Many new companies have tightened the company's competition in getting investors. Therefore, companies must have good performance and determine the correct financial ratios to have high corporate value because high corporate value affects a company's stock price and can increase market confidence. This study aims to determine the influence of Profitability Ratios on Firm Value, determine the effect of Firm Size on Firm Value, and determine how much influence Profitability Ratios and Firm Size have on Firm Value in Automotive and Components Sub Sector Manufacturing Companies Listed on the Indonesia Stock Exchange. This study uses a quantitative approach with an associative approach, which can be interpreted as a research method based on the philosophy of positivism, used to examine specific populations or samples. The population in this study is in the automotive and component sub-sector manufacturing companies listed on the Indonesian stock exchange for the 2016-2020 period, while the sample is 60 respondents in automotive and component manufacturing sub-sector companies listed on the Indonesian stock exchange. The results of this study indicate that Profitability Ratios and Firm Size have a positive and significant influence on Firm Value in Automotive and Components Sub Sector Manufacturing Companies Listed on the Indonesia Stock Exchange for the 2016-2020 period.